The influence of social media in increasing customer trust in m-commerce / Nurulhuda Azizi - Azizi, Nurulhuda (2015)
Social media generally refer to media used to enable social interaction. Customer behaviors are changing with the influence of social media and smart phones nowadays. Trust has been stated to be a significant factor influencing the acceptance of mobile commerce services. With the increase usage of mobile users browsing social media every day, social media and customer trust become a new research area to be explored. The aim of this study is to identify the influence of social media in increasing customer trust in M-Commerce. This study focuses on four factors; interactivity, platform quality, security and transparency. Data were collected using survey questionnaires which were carried out among 200 of mobile users in Malaysia. All the accumulated data was processed using Statistical Package for the Social Science (SPSS). Pearson correlation and ANOVA analysis were used to test the research questions. The findings provide evidence that security is the most dominant factor that influences the customer trust in M-commerce websites. It is also proven that level of customer trust is high among mobile users. The results also shown that three of the factors have significant relationship towards customer trust, while only transparency displayed low significant relationship.